2017
DOI: 10.1002/anie.201611006
|View full text |Cite
|
Sign up to set email alerts
|

Oxalyl Boronates Enable Modular Synthesis of Bioactive Imidazoles

Abstract: Described herein is the preparation of oxalyl boronate building blocks and their application for the construction of heterocycles. The oxalyl unit, readily accessible through commercially available starting materials, enables a modular approach for the synthesis of imidazoles. A variety of aromatic, heteroaromatic, and alkyl carboxaldehydes were condensed with oxalyl boronates to afford substituted boryl imidazoles in a regiocontrolled fashion. Subsequent palladium-catalyzed cross-coupling with haloarenes furn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 62 publications
1
38
0
4
Order By: Relevance
“…A variety of other heterocycle-forming reactions have also been developed using MIDA boronate-containing substrates. Making use of kinetically amphoteric molecules containing MIDA boronates and electrophilic ketones/aldehydes, Yudin has developed syntheses of borylated pyridazines/pyrroles, 156 imidazoles, 148 thiazoles, 149 imidazo[1,2-a]pyridines, 157 and many other motifs. 158 Watson has also developed a synthesis of 2-borylated indoles/benzofurans involving a palladium catalyzed cascade reaction with ethynyl BMIDA and 2-iodoanilines.…”
Section: Advances Towards a General Platform For Iterative Small Molementioning
confidence: 99%
“…A variety of other heterocycle-forming reactions have also been developed using MIDA boronate-containing substrates. Making use of kinetically amphoteric molecules containing MIDA boronates and electrophilic ketones/aldehydes, Yudin has developed syntheses of borylated pyridazines/pyrroles, 156 imidazoles, 148 thiazoles, 149 imidazo[1,2-a]pyridines, 157 and many other motifs. 158 Watson has also developed a synthesis of 2-borylated indoles/benzofurans involving a palladium catalyzed cascade reaction with ethynyl BMIDA and 2-iodoanilines.…”
Section: Advances Towards a General Platform For Iterative Small Molementioning
confidence: 99%
“…Yudin is interested in the development of new classes of amphoteric molecules for applications such as synthesis of heterocycles, orally bioavailable cyclic peptides, and boron‐containing therapeutics. His report on oxaloyl boronates for the synthesis of bioactive imidazoles is published in this issue …”
Section: Awarded …mentioning
confidence: 99%
“…[1] Increasingly,o rganoboronates find use as selective inhibitors of clinically relevant biological processes,ratiometric sensors for key analytes,and 18 F-labeled radioprosthetic groups for PET imaging. [1] Increasingly,o rganoboronates find use as selective inhibitors of clinically relevant biological processes,ratiometric sensors for key analytes,and 18 F-labeled radioprosthetic groups for PET imaging.…”
mentioning
confidence: 99%
“…Top: Previous routes to acylboronates. [18] Ab rief optimization study on the dihydroxylation reaction demonstrated that the use of buffered aqueous conditions (phosphate,p H7)d ramatically suppresses the hydrolysis of the critically needed MIDAe ster (see below). [15] ever,t he latter method requires air-sensitive glove-box techniques.Surprisingly,nomention of subsequent oxidation was made in either of these antecedent studies.I ns ummary, methods for preparing acylboronates have so far required multistep procedures,o fw hich several rely on the use of highly basic boryl or carbon anions,w hich restricts the reaction scope to as mall number of base-tolerant functional groups and substrates.…”
mentioning
confidence: 99%